Relationship Between Family Support and the Level of Utilization of Elderly Posyandu in the Working Area of Mongeudong Health Center, Banda Sakti Subdistrict, Lhokseumawe City, 2025 - Rohana Rohana; Linda Adriani; Wahyuni Wahyuni; Zuheri Zuheri (Lembaga Pengembangan Kinerja Dosen, 2025)
Posyandu lansia is a community-based health service effort aimed at improving the quality of life for the elderly thru regular health monitoring. However, the utilization rate of posyandu is still influenced by various factors, including family support. This study aims to determine the relationship between family support and the level of utilization of elderly health posts in the Mongeudong Health Center Work Area, Banda Sakti District, Lhokseumawe City in 2025. This study uses a descriptive analytic design with a cross-sectional approach. The study population consisted of all elderly individuals registered at the elderly health post, totaling 22 people. A sample of 22 respondents was selected using the total sampling technique. The research instruments are a family support questionnaire and a questionnaire on the utilization of elderly Posyandu. Data analysis was performed using univariate and bivariate methods with the Chi-Square test at a significance level of α = 0.05. The research results show that out of 21 respondents with family support, 16 people (33.3%) actively utilize the Posyandu. Conversely, out of 27 respondents without family support, 21 people (43.8%) are passive. Statistical tests show a ρ value of 0.001 < α (0.05), which means there is a significant relationship between family support and the utilization of elderly health posts. There is a significant relationship between family support and the level of utilization of elderly Posyandu. Elderly individuals with good family support tend to be more active in participating in Posyandu activities. It is recommended that families play a more active role in accompanying the elderly, and that community health centers strengthen family education programs to increase participation in Posyandu.